2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Transportation -- Motor Carrier Safety Regulations for Drivers of Farm Trucks [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Motor Carrier Safety Regulations establish safety and licensing standards for trucks, buses, and semi-trailers where gross vehicle weight exceeds 10,000 pounds. This is EDIS document FE417, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.